Hydroboration of Graphene Oxide: Towards Stoichiometric Graphol and Hydroxygraphane. Issue 22 (15th April 2015) - Poh, Hwee Ling; Sofer, Zdeněk; Šimek, Petr; Tomandl, Ivo; Pumera, Martin
Abstract Covalently functionalized graphene materials with well‐defined stoichiometric composition are of a very high importance in the research of 2D carbon material family due to their well‐defined properties. Unfortunately, most of the contemporary graphene‐functionalized materials do not have this kind of defined composition and, usually, the amount of heteroatoms bonded to graphene framework is in the range of 1–10 at. %. Herein, we show that by a well‐established hydroboration reaction chain, which introduces BH2 groups into the graphene oxide structure, followed by H2O2 or CF3COOH treatment as source of OH or H, we can obtain highly hydroxylated compounds of precisely defined composition with a general formula (C1O0.78H0.75)n, which we named graphol and highly hydroxylated graphane (C1(OH)0.51H0.14)n, respectively. These highly functionalized materials with an accurately defined composition are highly important for the field of graphene derivatives. The enhanced electrochemical performance towards important biomarkers as well as hydrogen evolution reaction is demonstrated.